Low carbon mobility and reducing automobile dependence - Newman, Peter (IET, 2017)
Low carbon mobility in our cities will need to be a combination of structural change that reduces automobile dependence as well as technological change. To determine the potential mechanisms for accelerating this transition, the emerging trends in reduced automobile dependence are outlined in the world's cities together with emerging technological trends. The policies outlined can enable 100% oil-free cities by 2050 and 100% renewably fuelled cities by 2100.